The component model for elementary landscapes and partial neighborhoods - Whitley, L. Darrell; Sutton, Andrew M.; Ochoa, Gabriela; Chicano-García, José-Francisco (My University, 2014)
Local search algorithms exploit moves on an adjacency graph of the search space. An “elementary landscape” exists if the objective function f is an eigenfunction of the Laplacian of the graph induced by the neighborhood operator; this allows various statistics about the neighborhood to be computed in closed form. A new component based model makes it relatively simple to prove that certain types of landscapes are elementary. The traveling salesperson problem, weighted graph (vertex) coloring and the minimum graph bisection problem yield elementary landscapes under commonly used local search operators. The component model is then used to efficiently compute the mean objective function value over partial neighborhoods for these same problems. For a traveling salesperson problem over n cities, the 2-opt neighborhood can be decomposed into ⌊n/2−1⌋ partial neighborhoods. For graph coloring and the minimum graph bisection problem, partial neighborhoods can be used to focus search on those moves that are capable of producing a solution with a strictly improving objective function value.
Theoretical Computer Science, 545, (2014), pp. 59-75
Keywords: Laplace, Operador de; Fitness landscape analysis; Stochastic local search; Elementary landscapes